PENGARUH PEMAHAMAN PAJAK, MOTIVASI MEMBAYAR PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI BATAM - Debbi Indriyani; Remista Simbolon (Jurnal Ekonomis, 2022)
This study aims to determine the understanding of taxation on individuals as well as how motivation to pay taxes and sanctions can affect taxpayer compliance in Batam City. In this study, the research approach used is a qualitative method. The technique of collecting research data was done by means of a questionnaire. The population is an individual taxpayer in Taman BPD Indah Batam Housing, Batam Centre. This study took a sample of 36 respondents. Data processing using SPSS v21.0 software. Using the correlation coefficient test, namely t test, coefficient of determination, coefficient of determination, simple regression, normality test, linearity test and multiple regression. Based on the data that has been analyzed by the author, Tax Understanding has no effect on Taxpayer Compliance. But the other variables, namely Motivation to Pay Taxes and Tax Sanctions on Taxpayer Compliance have a high influence. From all the data that has been processed, the writer concludes that the X variable dominantly affects the Y variable. So understanding of taxes, motivation to pay taxes and tax sanctions can be said to have a significant influence on individual taxpayer compliance in Batam.